DIAGNOSTICS OF THE LEVEL OF REFLECTION AMONG STUDENTS IN THE PROCESS OF STUDYING THE ACADEMIC DISCIPLINE "HUMAN LIFE SAFETY" (EDUCATION IN THE 21ST CENTURY, 2023)
The purpose of the study is to determine the significance of the phenomenon of reflection in the formation of the culture of life safety and a healthy lifestyle of young people. In the context of modernization of higher education and in connection with the needs of a changing society, there is a need for future specialists to apply the acquired knowledge, skills and abilities in practical activities, including in emergency situations of social, natural and technogenic nature. The relevance of the problem of forming students' reflection is due to the need to study the formation of reflective competence in the educational and pedagogical process in the preparation of specialists in various fields. But regardless of the areas of activity of future specialists, the main indicators of professional reflection are the ability to analyze, identify and evaluate personal values, knowledge, skills and abilities for self-realization and adaptation to changing environmental conditions and maintaining good health. The scientific novelty of the research topic is due to the need to find a mechanism for the formation of a culture of life safety and a healthy lifestyle with the help of a certain skill, the ability to reflect, understanding the importance of a health and personal safe behavior culture. Diagnostics of the level of reflection in students in the process of mastering the discipline "Human Safety" is a kind of marker for determining the formation of behavior skills in emergency situations, the ability to adequately assess the risks of negative threats, bad habits for health and understanding the importance of the value of their own life and those around. Reflection as a psychological property of the individual, closely related to the cognitive, intellectual and personal qualities of the individual, is an indicator of social activity, a tool for understanding oneself, the world around and a kind of trigger for the formation of a culture of life safety and a healthy lifestyle. Diagnosing the level of reflection in students helps to determine the characteristics of behavioral styles and the expected results of decisions made whenever events occur, sometimes fateful for one particular person, group of people or country.
Keywords: reflection; culture; life safety; healthy lifestyle; students